2020
DOI: 10.1177/1469787420908209
|View full text |Cite
|
Sign up to set email alerts
|

Who stands to benefit? Wellbeing, belonging and challenges to equity in engagement in extra-curricular activities at university

Abstract: Naomi Winstone is a Reader in Higher Education at the University of Surrey. As a cognitive psychologist, her research focuses on the application of psychological theory to higher education research, particularly in the areas of assessment and feedback, and student transitions.Kieran Balloo is a Lecturer in the Department of Higher Education at the University of Surrey. His research broadly focuses on scrutinising the 'student experience' through examining: student transitions; how students regulate their own a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The contribution of ECAs to the development of social and psychological resources that help the mental well-being of students has also been analyzed [14,26,27]. An increasing number of studies have found a significant positive relationship between engagement in extracurricular activities and extraversion (i.e., sociability and positive emotionality).…”
Section: Role Of Social Interactions In Developing An Ecamentioning
confidence: 99%
See 3 more Smart Citations
“…The contribution of ECAs to the development of social and psychological resources that help the mental well-being of students has also been analyzed [14,26,27]. An increasing number of studies have found a significant positive relationship between engagement in extracurricular activities and extraversion (i.e., sociability and positive emotionality).…”
Section: Role Of Social Interactions In Developing An Ecamentioning
confidence: 99%
“…An increasing number of studies have found a significant positive relationship between engagement in extracurricular activities and extraversion (i.e., sociability and positive emotionality). This extraversion is positively related to a higher psychological sense of community, greater involvement in campus activities and subjective wellbeing [14,27]. Therefore, ECAs are considered suitable for boosting confidence [19,28], sense of belonging [29], self-esteem [30], and positive self-concept [31], as well as developing emotional skills that enable a more positive attitude toward self and others [1].…”
Section: Role Of Social Interactions In Developing An Ecamentioning
confidence: 99%
See 2 more Smart Citations
“…While it is widely accepted that extracurricular activities (ECAs) enhance the student experience, and there is a growing body of literature on their role in aiding the socialisation process and fostering a sense of belonging at university (Tieu et al, 2010), their value in enhancing employability is less well-documented (Winstone et al, 2020). The literature that does exist indicates that ECAs can be beneficial for social networking, developing skills and improving employability (Stevenson and Clegg, 2011;Clark et al, 2015).…”
Section: Introductionmentioning
confidence: 99%